Neurocardiovascular instability may modulate end-organ damage: A review of this hypothesis investigating the eye and manifestations of NCVI. - Mc Garrigle, Christine; Kenny, Rose (My University, 2015)
Neurocardiovascular instability (NCVI) represents age-related changes in blood pressure and heart rate behaviour. It has been associated with increased leukoaraiosis in the brain and also conditions which are likely to be are related to cerebral end-organ damage, such as stroke and falls. The eye is a 'window' into the brain and cardiovascular (CV) system, changes in retinal microvasculature being independently predictive of cardiovascular events. The eye is highly vascular, having two circulatory systems and as such the ideal target end-organ to investigate NCVI and early end-organ damage. The retinal and choroidal circulations of the eye would be vulnerable to NCVI if ocular vasoregulation becomes impaired with age, particularly given the high metabolic activity of the retina. The choroid is predominantly extrinsically regulated by the autonomic nervous system. In patients with NCVI, autonomic dysfunction is more common and thus impairment of the tightly regulated ocular microcirculation may indeed be compromised. We review the evidence for the hypothesis that NCVI may modulate end-organ cardiovascular pathology and that the eye is the ideal target organ to monitor this.
PUBLISHED
Keywords: Ageing